The Effect of Accountability and Transparency of Regional Financial Management on Local Government Performance - Jeriansyah, Wan; Mappanyukki, Ratna (International Journal of Asian Social Science, 2020)
This study aims to determine the effect of accountability and transparency of regional financial management on local government performance at the Inspectorate of the Special Capital Region of Jakarta (DKI Jakarta Province). This study used primary data and the data obtained through a questionnaire method which involved 265 people as the population. The sampling technique used non-probability sampling techniques so that the samples in this study were 80 people. The technical analysis of the data used the SmartPLS version 3.0 programs. The results of this study indicated that the accountability and transparency of regional financial management have a positive and significant effect on local government performance.